KEMAMPUAN KOMUNIKASI MATEMATIS SISWA TUNARUNGU PADA PEMBELAJARAN MATEMATIKA DI SMPLB-B PKK PROVINSI LAMPUNG - Hidayat, Rifky; Suherman, Suherman (FKIP Universitas Lampung, 2016)
Mathematical Communication Ability of Deaf Students in Mathematics Learning in SMPLB-B PKK of Lampung Province. The obstacles encountered during the implementation process of mathematics learning in inclusive junior high school B of Family Welfare Guidance (SMPLB-B PKK) Lampung is the disruption of communication between students and teachers or vice versa. The purpose of this study was to determine the ability of mathematical communication of deaf students in mathematics learning. Stages of this qualitative descriptive study included an observation, interviews, documentation and triangulation using a handycam recording device. The data used in this research was the data analysis by Miles and Huberman model. The results showed that the students feel more comfortable in receiving learning with lecture method of sign language- based, oral method (speech), and writing, but an understanding of concepts and mathematical ability of deaf students is still relatively low. Keywords: mathematical communication, signaling system, the deaf DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601